24.8k views
3 votes
Solve:
-2x + 5y = -1
4x - 2y = -6

User Sufinawaz
by
4.5k points

1 Answer

2 votes

Answer:

(-2, -1)

Explanation:

Let's eliminate x using addition / subtraction. Multiply the entire first equation by 2, obtaining the following result:

-4x + 10y = -2

4x - 2y = -6

--------------------

8y = -8, and so y = -1.

Substituting -1 for y in the 2nd equation, we get:

4x - 2(-1) = -6, or

4x + 2 = -6, or

4x = -8, and so x = -2.

The solution to this system is (-2, -1).

User Namiko
by
5.2k points